A highly water-resistant single-component strong penetrating paste-like tile adhesive and its preparation process

By controlling the ratio of the binder emulsion and inorganic filler and using inorganic filler coated with a porous regenerated cellulose layer, the problem of the deterioration of the bonding strength of the paste-like ceramic tile glue under high temperature and high humidity conditions is solved, and good initial viscosity and stickiness are achieved.

CN118993614BActive Publication Date: 2025-03-07WUHAN DOBONS BUILDING MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411113460.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-03-07
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

It is difficult for existing paste-shaped ceramic tile glue to have both good initial viscosity and good bonding performance under humid and heat environments, especially the problem of decreasing bonding strength under high temperature and high humidity conditions.

Method used

By controlling the ratio of the binder emulsion and the inorganic filler, an inorganic filler coated with a porous regenerated cellulose layer is used to improve the coating strength and compatibility between the inorganic filler and the binder emulsion, and the moisture absorption swelling of the regenerated cellulose layer is replaced by moisture absorption swelling of the binder emulsion, thereby improving the bonding performance of ceramic tile glue under high temperature and high humidity conditions.

Benefits of technology

It has achieved good bonding performance of ceramic tile adhesive under high temperature and high humidity conditions, which far exceeds the 0.5N/mm2 shear bonding strength required by the national standard, ensuring the initial adhesion and stickiness of ceramic tile adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a highly water-resistant single-component strong penetrating paste-like tile adhesive and a preparation process thereof. The tile adhesive comprises at least the following components by mass: 100-200 parts of adhesive emulsion; 650-850 parts of inorganic filler; 50-150 parts of water; 3-15 parts of thickener; wherein the inorganic filler comprises a coarse filler and a fine filler, the coarse filler comprises coarse inorganic particles with a particle size of 250-800 μm and a coarse regenerated cellulose layer coated on the coarse inorganic particles, the fine filler comprises fine inorganic particles with a particle size of 100-150 μm and a fine regenerated cellulose layer coated on the fine inorganic particles, and the coarse regenerated cellulose layer and the fine regenerated cellulose layer are both distributed with hygroscopic pores. The present application has the effect of achieving both good initial adhesion and good bonding performance in a hot and humid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of tile adhesive, and in particular to a highly water-resistant single-component strong penetrating paste-like tile adhesive and a preparation process thereof. Background Art

[0002] Ceramic tile adhesive is mainly used for laying ceramic tiles, wall tiles, floor tiles and other decorative materials. It is widely used in interior and exterior walls, floors, bathrooms and kitchens and other architectural decorative places. Its main features are high bonding strength, excellent water resistance, freeze-thaw resistance, aging resistance and convenient construction. It is a relatively ideal paving adhesive material. Ceramic tile adhesive reduces the dependence of traditional construction technology on the base sprinkling and brick dipping process, and better avoids paving defects caused by insufficient brick dipping and sprinkling.

[0003] Domestic ceramic tile adhesives are mainly cement-based adhesives, as well as a small number of epoxy adhesives and emulsion-based adhesives. Since the traditional laying method is to lay ceramic tiles with a thick layer of cement mortar, about 1040 billion tons of sand and cement are consumed each year; while the new ceramic tile adhesive is laid with a thin layer, which consumes less than 250 billion tons of sand and cement, greatly saving resources.

[0004] For example, the patent application document with application number WO2024023063A1 discloses a ground slag-based tile adhesive, which comprises at least one aggregate and a hydraulic binder preparation, wherein the hydraulic binder preparation comprises: greater than 5% by weight of ground granulated blast furnace slag, preferably up to 30% by weight of calcium sulfate, 5% by weight or less of ordinary Portland cement, 10% by weight or less of cement containing calcium sulfoaluminate, clinker containing calcium sulfoaluminate, calcium aluminate cement or a mixture thereof, at least one complexing and thickening polymer selected from carboxymethyl cellulose, gum arabic, guar gum, guar ether, agar, carrageenan, xanthan gum, chitosan, pectin, and at least one rheology modifier, such as cellulose ether different from the complexing and thickening polymer.

[0005] The earliest ceramic tiles had a relatively high water absorption rate, and the back of the ceramic tiles had a large number of tiny capillary structures. Usually, cement paste or cement mortar is used to directly lay tiles on porous substrates. The bonding force comes from the cement paste penetrating into the surface capillaries and forming a tensile force similar to mechanical anchoring after drying to bond the ceramic tiles to the substrate. However, with the rapid development of indoor and outdoor wall finishes of buildings, a large number of low-water absorption and large-sized finishing materials have appeared on the market, such as ceramic thin plate tiles, vitrified tiles, polished tiles, microcrystalline stones, artificial marble, ceramic rock slabs, etc., and the paving materials have also developed from cement mortar to tile adhesive and tile back adhesive. As the water absorption rate of ceramic tiles is getting lower and lower, the pasting surface is becoming smoother and denser, and effective mechanical embedding cannot be provided. The use of traditional paving is even more unable to meet the bonding requirements, especially vitrified tiles and polished tiles have high material strength, are sensitive to temperature changes, and the temperature difference is not synchronized. Different from the thermal expansion coefficient of cement, there are temperature difference stress and seasonal temperature difference oscillation after large-sized ceramic tiles are laid. It will cause the bonding strength to decrease and destroy the bonding strength between the brick body and the substrate, resulting in hollowing between the tiles and the structural layer due to poor adhesion and bonding. Cement mortar is a rigid material with good durability but low bonding strength, and it cannot resist shedding due to thermal expansion and contraction or swelling and shrinkage.

[0006] Compared with cement-based tile adhesive, paste tile adhesive (type D tile adhesive) does not require pre-mixing and is a type of tile adhesive that is very easy to construct. Construction workers do not need to worry about the mixing ratio of powder and liquid to obtain a product that is dust-free and can be used directly. It is precisely because of its dust-free properties that it is an ideal choice for interior decoration. However, paste tile adhesives generally contain hydrophilic polymers such as acrylic polymers. These polymer particles can penetrate deeply into porous substrates to obtain good adhesion. However, these hydrophilic polymers have the inherent defect of water absorption and swelling after film formation. For example, GB / T41059-2021 Technical Requirements for Ceramic Tile Adhesives requires that ordinary paste emulsion-based adhesives (type D1 tile adhesives) have a resistance of not less than 1.0N / mm 2 However, even for the enhanced paste emulsion-based adhesive (D2 tile adhesive), the shear bond strength after 7 days of immersion in water under 21 days of curing is only required to be no less than 0.5N / mm 2 .

[0007] In the paste-like tile adhesive, if the proportion of polymer emulsion is increased, the good bonding performance of polymer emulsion can make the paste-like tile adhesive have good initial adhesion, so as to meet the paving requirements of low water absorption and large-sized finishing materials; however, the increase in the proportion of polymer emulsion often leads to an increase in the degree of water absorption and swelling of the adhesive film, and a decrease in the bonding strength after immersion in water. The long-term high temperature and high humidity environment such as the rainy season in the south puts forward higher requirements for the bonding strength of the paste-like tile adhesive. Therefore, obtaining a paste-like tile adhesive with both good initial adhesion and good bonding performance in a hot and humid environment is a technical problem that needs to be solved urgently but is difficult to solve. Summary of the invention

[0008] In order to improve the problem that the currently common paste-type tile adhesive is difficult to achieve both good initial adhesion and good bonding performance in a hot and humid environment, the present application provides a highly water-resistant single-component strong penetrating paste-type tile adhesive and a preparation process thereof.

[0009] The present application provides a highly water-resistant single-component highly penetrating paste-like tile adhesive and its preparation process using the following technical solutions:

[0010] In the first aspect, the present application provides a highly water-resistant single-component strong penetrating paste-like tile adhesive, which adopts the following technical solution:

[0011] A highly water-resistant, single-component, highly penetrating paste-like tile adhesive comprises at least the following components in parts by mass: 100-200 parts of an adhesive emulsion; 650-850 parts of an inorganic filler; 50-150 parts of water; and 3-15 parts of a thickener. The inorganic filler comprises a coarse filler and a fine filler, wherein the coarse filler comprises coarse inorganic particles with a particle size of 250-800 μm and a coarse regenerated cellulose layer coated on the coarse inorganic particles, and the fine filler comprises fine inorganic particles with a particle size of 100-150 μm and a fine regenerated cellulose layer coated on the fine inorganic particles, and both the coarse regenerated cellulose layer and the fine regenerated cellulose layer are provided with moisture absorbing pores.

[0012] By adopting the above technical solution, due to environmental protection requirements, all kinds of coatings and adhesives are currently water-based materials, and paste tile adhesives are no exception. Therefore, when preparing paste tile adhesives, the emulsion used must also be a hydrophilic polymer. However, the water resistance of paste tile adhesives prepared with water-based emulsions is often poor. For this reason, as mentioned above, these hydrophilic polymers have the inherent defect of water absorption and swelling after film formation. For example, in the GB / T41059-2021 ceramic tile adhesive technical requirements, ordinary paste emulsion-based adhesives are required to have a resistance of not less than 1.0N / mm 2 However, even for the enhanced paste-like emulsion-based adhesive, the shear bond strength after curing under standard conditions for 21 days and immersion in water for 7 days is only required to be no less than 0.5N / mm 2 .

[0013] It is generally believed that in order to improve the bonding performance of paste-like tile adhesive, it is effective to increase the proportion of adhesive emulsion in the formula. However, the inventors of this application have found that by appropriately increasing the proportion of adhesive emulsion, the initial adhesion and sustained adhesion of tile adhesive can indeed be improved. However, when the tile adhesive is under high temperature and high humidity conditions (such as the common plum rain season in the south, with high temperature, high humidity, and even soaking in condensed water for a long time), its bonding performance will be significantly reduced. In response to this phenomenon, the shear bonding strength of the tile adhesive after 7d immersion in water was tested according to the test standard of D2 (enhanced paste emulsion-based adhesive) in the technical requirements of GB / T41059-2021 ceramic tile adhesives, and it was found that the bonding performance of the tile adhesive was significantly reduced compared to its dry conditions. However, if the proportion of adhesive emulsion in the formula is reduced, the initial adhesion and sustained adhesion of the tile adhesive will decrease accordingly, and it is difficult to pass the anti-slip test in the national standard GB / T41059-2021. This is why the current national standard GB / T41059-2021 requires the shear bond strength of ordinary paste emulsion-based adhesives (D1) to be no less than 1N / mm. 2 For D2 tile adhesive with higher requirements, the shear bonding strength after 7 days of immersion in water is not less than 0.5N / mm 2 That is because it is difficult to have both.

[0014] Based on this problem, the inventors of the present application found that by controlling the ratio of the binder emulsion and the inorganic filler, while controlling the grading of the inorganic filler and coating the inorganic filler with a regenerated cellulose layer with a porous structure, the tile adhesive can not only have initial adhesion and lasting adhesion compared to conventional tile adhesives, but also have good adhesion even under high temperature and high humidity conditions that are not required by the national standard GB / T41059-2021. This is a very unexpected result.

[0015] The improvement in initial adhesion and sustained adhesion may be due to the fact that the inorganic filler accounts for a relatively high proportion in the paste-like emulsion-based tile adhesive formula in the present application. Although the surface of the inorganic filler is coated with the adhesive emulsion, when laying tiles, the adhesive emulsion on the surface of the inorganic filler that is in contact with the tile is easily squeezed away, making the thickness of the adhesive emulsion between the inorganic filler and the tile too thin, or even causing the inorganic filler to directly contact the tile. In either case, the bonding performance will be reduced. By controlling the addition amount of the adhesive emulsion to 100-200 parts and the addition amount of the inorganic filler to 650-850 parts, and controlling the inorganic filler to include coarse filler and fine filler, wherein the particle size of the coarse inorganic particles in the coarse filler is 250-800μm, and the particle size of the fine inorganic particles in the fine filler is 100-150μm, and filling the gaps between the coarse fillers with the fine fillers, the movement resistance of the adhesive emulsion during the paving of the tile adhesive can be increased, thereby increasing the thickness of the adhesive emulsion covering the surface of the tile after paving, and, under the specific particle size grading of the present application, the tile adhesive has good initial adhesion and sustained adhesion.

[0016] On the basis of using special graded inorganic fillers, on the one hand, the inorganic filler surface has a regenerated cellulose layer, and cellulose has a large number of hydroxyl groups. These hydroxyl groups can form hydrogen bonds with each other and with the binder emulsion in the formula. The hydrogen bonds formed between the regenerated cellulose layer and the binder emulsion can well ensure that the binder emulsion is stably coated on the surface of the inorganic filler during the paving process, thereby greatly reducing the possibility that the inorganic filler directly contacts the tile and causes the bonding performance to decrease. On the other hand, the regenerated cellulose layer has a large number of hygroscopic pore structures. The pore structures with larger pore diameters in these hygroscopic pores absorb the binder emulsion in the formula through capillary phenomena, thereby further improving the compatibility and coating fastness between the binder emulsion and the inorganic filler. Even if the binder emulsion on the surface of the inorganic filler is squeezed so that the inorganic filler directly contacts the tile, the large number of hydroxyl groups on the regenerated cellulose layer can easily form hydrogen bonds with the inorganic material on the tile to obtain good initial adhesion.

[0017] Furthermore, in a high temperature and high humidity environment, an inorganic filler with an added amount far greater than that of the binder emulsion and having a regenerated cellulose layer on the surface has a significantly better moisture absorption capacity than the binder emulsion due to the large number of hydrophilic hydroxyl groups on the surface of the regenerated cellulose layer. It can thus capture water from the binder emulsion, thereby greatly reducing the possibility of a decrease in viscosity due to the polymer particles in the binder emulsion absorbing moisture. Of course, the regenerated cellulose layer will also swell after absorbing moisture. However, the regenerated cellulose layer has a large number of hygroscopic pore structures. The large number of pore structures provide deformation space for the moisture absorption and swelling of the regenerated cellulose layer, which greatly reduces the possibility of a decrease in viscosity due to moisture absorption and swelling of the tile adhesive. This allows the tile adhesive of the present application to have good bonding properties even in a high temperature and high humidity environment, which is far greater than the 0.5N / mm required in the national standard GB / T41059-2021. 2 .

[0018] In summary, the grading of inorganic fillers controls the possibility of the binder emulsion on the coarse filler and the fine filler being squeezed off the inorganic filler during the paving process, thereby obtaining good initial adhesion and sustained adhesion; and the regenerated cellulose layer with hygroscopic holes evenly distributed on the inorganic filler can greatly improve the coating strength between the inorganic filler and the binder emulsion, and can also replace the hygroscopic swelling of the binder emulsion by the hygroscopic swelling of the regenerated cellulose layer. With the pinning effect of the specially graded inorganic filler, the tile adhesive produces less swelling under high temperature and high humidity conditions, so as to obtain good bonding performance under high temperature and high humidity conditions.

[0019] It is particularly important to note that adding cellulose fiber to the formula of tile adhesive cannot obtain initial adhesion and high temperature and high humidity conditions; in addition, the D2 standard in the national standard GB / T41059-2021 tests the high-temperature shear bond strength of tile adhesive and the shear bond strength after 7d immersion in water, respectively, and does not require testing the shear bond strength of tile adhesive under high temperature and high humidity conditions. However, during the rainy season in the south, tile adhesive is actually at higher temperatures and higher humidity for a long time.

[0020] In addition, the so-called adhesive emulsion in this application is in liquid state when it is prepared, but when discussing its hygroscopicity, strength, etc., it refers to the state after it is dried and formed into a film; similarly, when discussing the performance of tile adhesive, it refers to the state of its dried film thickness. Therefore, the so-called regenerated cellulose takes water from the adhesive emulsion, and it takes water from the liquid adhesive emulsion, but takes water from the adhesive emulsion (although it is called an emulsion, it is a solid state) in the cured film-forming tile adhesive.

[0021] Optionally, in the inorganic filler, the mass ratio of the inorganic particles to the regenerated cellulose layer is 10:2-3.

[0022] By adopting the above technical solution, the inorganic filler in the paste-like tile adhesive plays a very important filling and strengthening role. The inorganic filler with a regenerated cellulose layer structure in the present application actually uses inorganic particles as a skeleton, and the surface is covered with a regenerated cellulose layer. Considering that the strength of the regenerated cellulose layer material itself is relatively low, the strength of the inorganic filler mainly depends on the inorganic particles as the skeleton. Therefore, the proportion of inorganic particles in the inorganic filler should not be too low, so as to avoid the overall strength of the inorganic filler being too low. Of course, if the proportion of the regenerated cellulose layer is too low, it is often difficult to play a good role in capturing water from the self-adhesive emulsion, making it difficult for the tile adhesive to ensure good viscosity under high temperature and high humidity conditions. In particular, if the proportion of the regenerated cellulose layer is too high, the regenerated cellulose layer on the surface is difficult to adhere well, which may cause the regenerated cellulose layer to fall off during the preparation process and use.

[0023] By controlling the ratio of the two to 10:2-3, the inorganic filler can have both good strength and good moisture absorption effect, so that the tile adhesive has good adhesion under high temperature and high humidity conditions.

[0024] Optionally, the average pore size of the moisture absorption pores is 50-200 nm, and the pore area of ​​the moisture absorption pores accounts for no less than 20%. Preferably, the pore area of ​​the moisture absorption pores accounts for no more than 60%.

[0025] By adopting the above technical solution, the size of the hygroscopic pores determines the adsorption effect of these pores on the binder emulsion on the one hand. If the hygroscopic pores are too small, it is difficult to adsorb the binder emulsion with a large viscosity, which leads to a decrease in compatibility between the binder emulsion and the inorganic filler, and a decrease in bonding strength; if the hygroscopic pores are too large, these pore structures will be basically filled with the binder emulsion and closed, and it is difficult to play a good role in absorbing moisture and replacing the deformation of the binder emulsion under high temperature and high humidity conditions. Therefore, it is necessary to control the average pore size of the hygroscopic pores to be 50-200nm and the pore area ratio to be not less than 20%, on the one hand to ensure the physical intercalation between the inorganic filler and the binder emulsion, improve compatibility and bonding strength, and on the other hand to ensure that the regenerated cellulose layer can take water from the binder emulsion and swell instead of it under high temperature and high humidity conditions, and when the regenerated cellulose layer swells, these hygroscopic pores with suitable pore size and a large pore area ratio provide a large amount of deformation space. Of course, the pore area ratio of the hygroscopic pores is preferably not more than 60%, which can ensure that the regenerated cellulose layer has sufficient hydroxyl groups that absorb water.

[0026] The average pore size of the moisture absorption pores is the average pore size of the moisture absorption pores on the coarse regenerated cellulose layer and the fine regenerated cellulose layer, and the pore area ratio is also.

[0027] Optionally, among the hygroscopic pores, those with a pore size greater than 150 nm are permeation pores, and those with a pore size not greater than 150 nm are swelling pores, and the number of the swelling pores accounts for a greater proportion than the number of the permeation pores.

[0028] By adopting the above technical scheme, the pores with a pore size greater than 150 nm in the moisture absorption pores are penetration pores, which are more conducive to the penetration of high-viscosity binder emulsions, thereby improving the bonding strength and compatibility between the inorganic filler and the binder emulsion, while the swelling pores with smaller pore sizes are difficult to adsorb high-viscosity binder emulsions, and are therefore retained during the preparation and use processes. When the regenerated cellulose layer absorbs moisture and swells, these swelling pores, which are small in pore size but account for a large proportion (the proportion of swelling pores is greater than the proportion of penetration pores, so the number of swelling pores accounts for the majority), can provide a good swelling space.

[0029] Optionally, the ratio of the swelling pores to the number of the hygroscopic pores is 55-70%, and the ratio of the pores with a pore diameter greater than 300 nm among the hygroscopic pores is 1-5%.

[0030] By adopting the above technical solution, the swelling pores accounting for no less than 55% can ensure that the regenerated cellulose layer has sufficient swelling space after absorbing moisture and swelling, while the remaining penetration pores, which are small in number but larger in diameter, can better ensure that the adhesive emulsion penetrates into the regenerated cellulose layer. On this basis, it is ensured that the pore structure has a pore size greater than 300nm and accounts for 1-5%, which can well form a small number of "anchor points" with high strength between the adhesive emulsion and the regenerated cellulose layer to strengthen the pinning effect of the inorganic filler in the tile adhesive, reduce the swelling and mutual displacement of the tile adhesive as a whole, thereby further reducing the moisture absorption and swelling of the tile adhesive, and making the tile adhesive have good viscosity under high temperature and high humidity conditions.

[0031] Optionally, 1-5 parts of bactericide, 1-5 parts of dispersant and 0.5-2 parts of defoamer are added to the tile adhesive in parts by mass.

[0032] By adopting the above technical solution, the performance of the tile adhesive can be further improved by appropriately adding bactericides, dispersants, defoamers, etc.

[0033] Optionally, the added mass ratio of the coarse filler to the fine filler is 1.5-3.5, the mass ratio of the inorganic filler to the effective mass of the binder emulsion is 8-13, and the effective mass of the binder emulsion is the product of the added mass of the binder emulsion and the solid content.

[0034] By adopting the above technical solution, on the basis that the particle size of the coarse inorganic particles in the coarse filler is 250-800μm and the particle size of the fine inorganic particles in the fine filler is 100-150μm, the added mass ratio of the two is further controlled to be 1.5-3.5, which means that the inorganic filler is mainly coarse filler, and the fine filler with a relatively small proportion is filled between the coarse filler, and the binder emulsion is coated on the coarse filler and the fine filler respectively. Such grading and proportioning can reduce the possibility of relative displacement between the coarse filler and the fine filler. In addition, the amount of binder emulsion added is less than that of the inorganic filler. In particular, the mass ratio of the effective mass of the inorganic filler to the binder emulsion is controlled to be 8-13, which can ensure that after the tile adhesive is dried and film-formed, the thickness of the binder emulsion coated on the inorganic filler is not too thick (the ratio of the two is not less than 8). On the one hand, this can ensure that the tile adhesive is not easy to swell greatly under high temperature and high humidity conditions. On the other hand, this can ensure that the regenerated cellulose layer has good water absorption to avoid the viscosity of the binder emulsion from decreasing after swelling. Of course, the ratio of the two should not be greater than 13, so as to avoid insufficient initial adhesion of the tile adhesive.

[0035] It should be noted that this ratio is based on the hygroscopic pore structure of the regenerated cellulose layer on the inorganic filler, and even if the regenerated fiber layer absorbs moisture, there will be no obvious swelling phenomenon. In addition, it is precisely because the regenerated cellulose layer has permeable pores and swelling pores, and the smaller swelling pores have a good capillary effect, which can ensure the water absorption effect of the regenerated cellulose layer with a thinner binder emulsion layer, while the bonding sites formed between the larger permeable pores and the binder emulsion can ensure the bonding strength of the inorganic filler and the binder emulsion.

[0036] In a second aspect, the present application provides a preparation process of a highly water-resistant single-component highly penetrating paste-like tile adhesive, which adopts the following technical solution:

[0037] A preparation process of a highly water-resistant single-component strong penetrating paste-like tile adhesive comprises the following process steps:

[0038] S1, preparation of inorganic filler, preparing a modifying liquid and respectively blending the coarse inorganic particles and the fine inorganic particles with the modifying liquid to obtain a slurry, then placing the slurry in a solidifying liquid to solidify the modifying liquid by phase separation, and then placing it in a regeneration bath to form a coarse regenerated cellulose layer covering the coarse inorganic particles and a fine regenerated cellulose layer covering the fine inorganic particles, to obtain an inorganic filler covered with a regenerated cellulose layer;

[0039] S2, mixing, according to the ratio, first preliminarily blend the binder emulsion and water to obtain a mixed emulsion, then heat the mixed emulsion to 50-70°C, then preliminarily blend the coarse filler and the fine filler into a mixed inorganic filler and add it to the heated mixed emulsion, the temperature of the inorganic filler is heated to 10-20°C higher than the temperature of the mixed emulsion, then add the remaining materials and stir evenly and cool to room temperature.

[0040] By adopting the above technical solution, in step S1, the modified liquid solidifies in the solidifying liquid in phase separation and forms a hygroscopic pore structure, so that the inorganic filler is covered with a regenerated cellulose layer with hygroscopic pores. It should be noted that since there are a large number of hydroxyl groups on cellulose and the inorganic filler itself is also easy to form hydroxyl groups, the inorganic filler and cellulose often have good coating strength.

[0041] In step S2, the materials are mixed according to the proportions, however, the mixing process is not a conventional mixing process. Instead, the diluted binder is firstly heated to obtain a mixed emulsion and heated to a higher temperature of 50-70°C, so that the viscosity of the mixed emulsion decreases, and the inorganic filler is heated to a higher temperature, and the temperature of the inorganic filler is heated to 10-20°C higher than the mixed emulsion, which can significantly improve the comprehensive performance of the final tile adhesive. This is because, by controlling the temperature of the two, on the one hand, the viscosity of the mixed emulsion is reduced by heating, making the mixed emulsion (the viscosity decreases after dilution, and the viscosity is even lower after heating) easier to penetrate into the moisture absorption pores to form anchor points between each other. On the other hand, the inorganic filler is controlled to have a higher temperature, so that when the two are mixed, the temperature of the mixed emulsion near the surface of the inorganic filler increases, and the mixed emulsion there has a further lower viscosity. The subsequent cooling behavior of the inorganic filler causes the pore structure on the regenerated cellulose layer to cool and shrink, forming a certain negative pressure, thereby forming a certain adsorption force on the mixed emulsion. The combination of multiple factors reduces the possibility of the mixed emulsion viscosity being too high, which makes it difficult for the inorganic filler and the adhesive emulsion to mechanically fit together, thereby obtaining a tile adhesive with better overall viscosity.

[0042] Optionally, the step S1 specifically includes the following steps:

[0043] S11, preparing a modifying liquid, wherein the modifying liquid comprises cellulose acetate, a porogen and a solvent, wherein the content of cellulose acetate in the modifying liquid is 10-15wt%, and the amount of the porogen added is 0.3-0.5 times the amount of the cellulose acetate added;

[0044] S12, mixing, filling the packing bed with the coarse inorganic particles or the fine inorganic particles, and then filtering the modified liquid with the packing bed to make the modified liquid adhere to the inorganic particles to obtain a slurry, and the temperature of the mixing process is controlled at 10-20° C.;

[0045] S13, solidification and phase separation, filtering the solidified liquid through a filler bed filled with slurry to promote phase separation and solidification of the modified liquid to obtain initial particles, wherein the solidified liquid is at least one of water, methanol and ethanol;

[0046] S14, post-treatment, placing the initial particles in a regeneration bath to hydrolyze the cellulose acetate and regenerate it into regenerated cellulose, wherein the regeneration bath is an aqueous sodium hydroxide solution.

[0047] By adopting the above technical solution, by controlling the ratio of each material in the modified liquid, especially the content of cellulose acetate in the modified liquid, and controlling the addition ratio of the porogen to cellulose acetate, it is possible to ensure that the final regenerated cellulose layer has the desired pore structure. By controlling the temperature during the mixing process to be low, only 10-20°C, it is possible to ensure that the modified liquid with higher viscosity at low temperature is better attached to the inorganic particles, and then in the curing and regeneration process, the desired porous regenerated cellulose layer is obtained by phase solidification.

[0048] It should be noted that in the present application, the inorganic filler adopts a special preparation process of filtration and adhesion. When the modified liquid is filtered by the packed bed filled with inorganic particles, the inorganic particles as fillers can be well and evenly contacted with the modified liquid, and the modified liquid with low solid content can be better adhered to the inorganic particles to form a uniform modified liquid layer by low temperature filtration. In the subsequent phase separation solidification process, the homogeneous modified liquid forms a solvent-rich phase and a polymer-rich phase, and due to the lower solid content and the adhesion of inorganic particles to the polymer-rich phase, the regenerated cellulose layer between adjacent inorganic filler particles during the phase separation solidification process often has only a small adhesion, and the adhesion is very easy to break. Therefore, the prepared inorganic filler is often a monodisperse particle coated with a regenerated cellulose layer, rather than a block of three-dimensional network regenerated cellulose filled with inorganic particles. That is, the main body finally obtained is inorganic particles, and the regenerated cellulose layer is only a layer structure coated on the inorganic particles, rather than regenerated cellulose as the main body, and inorganic particles are dispersed in the regenerated cellulose. Of course, the mass ratio of the inorganic particles to the regenerated cellulose layer is calculated based on the initial weight of the inorganic particles and the weight of the inorganic filler finally obtained.

[0049] If the more common blending process is adopted to directly blend the modified liquid and inorganic particles, it is often difficult to ensure the uniformity of the mixing of the inorganic particles and the modified liquid, and the inorganic filler finally obtained often has poor uniformity. In addition, if the solid content of the modified liquid is too high, although the viscosity of the modified liquid is higher and it is easy to adhere to the inorganic particles, the content of the polymer-rich phase increases during phase separation and solidification. On the one hand, the adhesion of the regenerated cellulose layers on adjacent inorganic particles increases, and it is not easy to obtain monodisperse inorganic filler particles. On the other hand, the proportion of the pore structure of the regenerated fiber layer decreases, making it difficult to achieve a good moisture absorption effect and a good anchoring effect with the binder emulsion.

[0050] In addition, since the modifying liquid and the phase separation process used to prepare the coarse filler and the fine filler are completely the same, the pore structures on the coarse regenerated cellulose layer and the fine regenerated cellulose layer are substantially the same.

[0051] Optionally, before step S13, the solvent vapor is filtered through a packed bed filled with slurry for 10-30 seconds. The solidifying liquid is a methanol aqueous solution, and the volume proportion of methanol is 20-30%.

[0052] By adopting the above technical scheme, the inventors of the present application found that by pre-treating the slurry and using a special methanol aqueous solution as the curing liquid, the final prepared paste-like tile adhesive can have better bonding performance under high temperature and high humidity conditions, which is an unexpected result that was not expected.

[0053] Before curing, the solvent vapor is filtered through a filler bed filled with slurry. The solvent vapor is adsorbed on the surface of the slurry, so that the surface of the slurry is diluted, and the modified liquid in the slurry forms a concentration gradient with thick inside and thin outside. During the subsequent curing, the modified liquid with lower concentration on the surface is easier to form a pore structure, thereby increasing the porosity of the final cellulose layer. Higher porosity means better compatibility with the remaining ingredients in the formula and better bonding strength (due to capillary adsorption effect, etc.). More importantly, higher porosity also means larger deformation space, which greatly reduces the possibility of decreased hygroscopic viscosity of the adhesive emulsion in the formula after the tile adhesive absorbs moisture under high humidity conditions.

[0054] In addition, by using a methanol aqueous solution with a volume concentration of 20-30% as the curing liquid, the methanol has a small molecular weight and a relatively small surface tension, which has a certain effect of helping penetration, and can make the curing liquid quickly penetrate and solidify the modified liquid inside the slurry after the modified liquid on the surface of the slurry is phase-separated and solidified. The faster the phase-separation solidification speed is, the less time the cellulose molecular chains have to rearrange and crystallize, and thus have a lower crystallinity. In particular, unlike the general expectation that the regenerated fiber layer has a higher crystallinity to obtain better anti-swelling properties and better mechanical strength; the present application hopes that the final regenerated cellulose layer has a properly reduced crystallinity. This is because the molecular chains in the crystalline region of the regenerated cellulose layer are arranged regularly, and the hydroxyl groups basically form hydrogen bonds between the molecular chains. Only the free hydroxyl groups in the amorphous region that have not formed hydrogen bonds between the molecular chains are more likely to form hydrogen bonds with the binder emulsion, with the water adsorbed under high humidity conditions, and with tiles, etc., and are therefore more likely to plunder water from the binder emulsion. Therefore, appropriately reducing the crystallinity of the regenerated cellulose layer can obtain better bonding properties, especially bonding properties under high humidity conditions.

[0055] In summary, the present application includes at least one of the following beneficial technical effects:

[0056] 1. The present application innovatively adds an inorganic filler coated with a porous regenerated cellulose layer into the ceramic tile adhesive formula, which not only ensures that the ceramic tile adhesive has good initial adhesion, but also has good adhesion even in a high temperature and high humidity environment that is more stringent than the national standard, thereby solving the current difficult problem of not being able to achieve both good initial adhesion and good bonding performance in a hot and humid environment;

[0057] 2. By further controlling the average pore size and pore area ratio of the moisture absorption pores, including the larger penetration pores and the smaller swelling pores, the penetration pores can further improve the bonding strength and compatibility between the binder emulsion and the inorganic filler, while the swelling pores are too small to easily absorb the high-viscosity binder emulsion, but they can provide swelling space under high temperature and high humidity conditions after curing and forming the film;

[0058] 3. By further preferably controlling the mass ratio of the inorganic filler to the effective mass of the binder emulsion to be 8-13, further preferred initial viscosity and good high temperature and high humidity working condition viscosity can be obtained;

[0059] 4. By adopting a special inorganic filler preparation process and a special mixing process, high compatibility and bonding strength between the inorganic filler and the binder emulsion can be ensured. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a schematic diagram of a scanning electron microscope of the regenerated cellulose layer on the surface of the inorganic filler in Preparation Example 1 of the present application, with a magnification of 20,000 times.

[0061] Figure 2 This is a schematic diagram of a scanning electron microscope of the regenerated cellulose layer on the surface of the inorganic filler in Example 3 of the present application, with a magnification of 20,000 times. DETAILED DESCRIPTION

[0062] The following is combined with Figure 1-2 This application is described in further detail.

[0063] Preparation example of inorganic filler

[0064] Preparation Example 1

[0065] The preparation process of inorganic filler includes the following process steps:

[0066] S11, preparing a modifying liquid, the modifying liquid comprising cellulose acetate, a porogen and a solvent, wherein the content of cellulose acetate in the modifying liquid is 12wt%, the amount of the porogen added is 0.4 times the amount of the cellulose acetate added, specifically, the content of the porogen is 4.8wt%, and the rest is solvent. In this embodiment, cellulose acetate is selected from diacetyl cellulose with an acetyl content of 39.7%, the porogen is PEG-8000, and the solvent is acetone.

[0067] S12, mixing, filling the packing bed with coarse inorganic particles or fine inorganic particles, and then filtering the modified liquid through the packing bed filled with inorganic particles, so that the modified liquid adheres to the inorganic particles to obtain a slurry. The temperature of the mixing process is controlled at 15°C. The so-called temperature of the mixing process, that is, the temperature when the packing bed is filtering the modified liquid, is controlled at 15°C. In this preparation example, the coarse inorganic particles are calcium carbonate with a particle size of 420μm, and the fine inorganic particles are calcium carbonate with a particle size of 120μm.

[0068] S13, solidification and phase separation, first filter the solvent vapor with a packed bed filled with slurry, the filtration time is 20s, and the modified liquid attached to the inorganic particles is prompted to adsorb the solvent vapor, thereby diluting the surface of the modified liquid; then filter the solidified liquid with a packed bed filled with slurry, and promote the modified liquid attached to the inorganic particles to solidify by phase separation to obtain initial particles; in this preparation example, the solvent vapor is saturated acetone vapor, and the solidifying liquid is a methanol aqueous solution with a volume concentration of 25%.

[0069] S14, post-treatment, placing the initial particles in a regeneration bath to hydrolyze the cellulose acetate and regenerate it into regenerated cellulose, wherein the regeneration bath is an aqueous sodium hydroxide solution; followed by multiple washings and drying.

[0070] Preparation Example 2-5

[0071] The main difference between Preparation Example 2-5 and Preparation Example 1 is that different inorganic particles and modifying liquids are selected and the preparation process is appropriately adjusted, as shown in the following table:

[0072]

[0073]

[0074] The parameters of the inorganic fillers obtained in each preparation example are detailed in the table below:

[0075]

[0076] In the above table, the inorganic particle / regenerated cellulose layer mass ratio is calculated by the difference in mass before and after the inorganic particle treatment, and is the average of the coarse filler and fine filler data; the average pore size is the average pore size of the hygroscopic pores on the regenerated cellulose layer on the surface of the inorganic filler, which is also the average of the coarse filler and fine filler data; the pore area ratio is the area ratio of the hygroscopic pores per unit area under the microscopic image, which can be measured manually or automatically using software such as image J; the macropore ratio refers to the ratio of pores with a pore diameter greater than 300nm in the hygroscopic pores.

[0077] It should be noted that, since a relatively high concentration of modifying liquid was used in Preparation Example 5 and the solvent vapor was not filtered before solidification and phase separation, the regenerated cellulose layer on the surface of the inorganic filler finally obtained was relatively dense and had no obvious pore structure, so there was no pore morphology parameter.

[0078] Embodiment of highly water-resistant one-component paste-like tile adhesive

[0079] Example 1

[0080] This embodiment discloses a highly water-resistant one-component paste-like tile adhesive, comprising the following raw materials in parts by weight:

[0081] 150 parts of binder emulsion, 537 parts of coarse filler, 220 parts of fine filler (757 parts of inorganic filler in total, coarse and fine filler mass ratio is 2.4), 1 part of thickener A, 8 parts of thickener B (9 parts of thickener in total), 3 parts of bactericide, 3 parts of dispersant, 1 part of defoamer, 85 parts of water. In this embodiment, the binder emulsion is BASF Acronal 5041ap, the inorganic filler adopts the inorganic filler prepared in Preparation Example 1, the dispersant is BASF DISPEX CX 4320, the thickener A is BASF RheovisAS 1130, the thickener B is Dow Walocel MW 15000PFV hydroxyethyl methylcellulose thickener, and the bactericide is Dow SILVADUR 930 polymer silver ion bactericide. Since the binder emulsion is BASF Acronal 5041ap with a solid content of 52%, in this embodiment, the mass ratio of the inorganic filler to the effective mass of the binder emulsion is 9.7.

[0082] The highly water-resistant one-component paste-like tile adhesive in this embodiment is prepared by the following process steps:

[0083] S1. Preparation of inorganic filler, see Preparation Example for details;

[0084] S2, mixing, according to the above ratio, first preliminarily blend the binder emulsion and water to obtain a mixed emulsion, then heat the mixed emulsion to 60°C, then preliminarily blend the coarse filler and the fine filler into a mixed inorganic filler and add it to the heated mixed emulsion, the temperature of the inorganic filler is heated to 15°C higher than the temperature of the mixed emulsion, that is, the temperature of the inorganic filler is 75°C, then add the remaining materials and stir evenly and cool to room temperature.

[0085] Embodiment 2-8

[0086] The main difference between Example 2-8 and Example 1 is that, on the one hand, the composition ratio of the tile adhesive is adjusted, and on the other hand, the preparation process of the tile adhesive is adjusted, as shown in the following table for details:

[0087]

[0088]

[0089] Comparative Example 1

[0090] The only difference between Comparative Example 1 and Example 1 is that the inorganic filler in the formula is replaced by an equal mass of coarse inorganic particles in Preparation Example 1 that have not been modified, and the fine filler in Preparation Example 1 is replaced by an equal mass of fine inorganic particles in Preparation Example 1 that have not been modified.

[0091] Comparative Example 2

[0092] The only difference between Comparative Example 2 and Example 1 is that the inorganic filler in the formula is replaced by the inorganic filler prepared in Preparation Example 1 with the inorganic filler prepared in Preparation Example 5 of the same mass.

[0093] Comparative Example 3

[0094] Comparative Example 3 is based on Comparative Example 1, with the addition of 10 parts by mass of nanocellulose, the nanofibers being purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd., and having a diameter of about 10-50 nm and a length of about 0.5-3 μm after dispersion.

[0095] Comparative Example 4

[0096] The only difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, no fine filler is added, but only coarse filler is added. Specifically, the fine filler in Example 1 is replaced by coarse filler in equal mass.

[0097] Comparative Example 5

[0098] The only difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, no coarse filler is added, but only fine filler is added. Specifically, an equal mass of the coarse filler in Example 1 is replaced by the fine filler.

[0099] Performance Testing

[0100] The tile adhesives prepared in the embodiments and comparative examples were used as samples, and various performance parameters of the tile adhesives were tested in accordance with the technical requirements of standard GB / T41059-2021 ceramic tile adhesives.

[0101] On the basis of the aforementioned national standard, a high temperature and high humidity test condition is added. Specifically, when testing the performance of "curing under standard conditions for 21 days, shear bonding strength after 7 days of immersion in water", the water temperature is controlled to be 50°C during the 7 days of immersion in water.

[0102] The test results are detailed in the table below:

[0103]

[0104]

[0105] In the above table, the unit of anti-slip performance is mm, and the unit of all adhesion performance parameters is mPa.

[0106] in conclusion

[0107] The tile adhesives prepared in Examples 1-3 have very good performance in terms of anti-slip performance, high temperature resistance, water immersion resistance, and even under high temperature water immersion conditions that are not required by the national standards, and their performance far exceeds the national standards.

[0108] By comparing Example 1 with Example 4, it is not difficult to find that, on the basis of the generally same overall ratio of the two, since the proportion of the regenerated cellulose layer on the filler of Preparation Example 2 used in Example 4 is relatively small, although its anti-slip performance and high temperature resistance are relatively good, its water resistance and high temperature water resistance are slightly lower than those of Example 1. Obviously, the proportion of the regenerated cellulose layer in the filler needs to be strictly controlled.

[0109] By further comparing Example 1 with Examples 5-8, it is not difficult to find that in Example 5, due to the use of the filler in Preparation Example 3, its regenerated cellulose layer has a significantly larger average pore size and a relatively low swelling pore ratio, which shows that Example 1 has significantly better final water immersion resistance and high temperature water immersion resistance. This should be because the larger pore structure on the surface of the filler in Example 5 was filled with the emulsion too early, resulting in the loss of the effect of providing swelling space for swelling after moisture absorption. Similarly, in Example 7, due to the use of the filler in Preparation Example 6, its average pore size, macropore ratio, etc. are too large, and the swelling pore ratio is too low, which shows that Example 1 has significantly better final water immersion resistance and high temperature water immersion resistance.

[0110] Example 6 has relatively low anti-slip performance, which may be due to the use of the filler in Preparation Example 4, which has too small a surface pore size and too low a macropore ratio, making it difficult to form a pinning effect with the high-viscosity emulsion, which is manifested as Example 1 having significantly better anti-slip performance and bonding performance. Similarly, in Example 8, due to the use of the filler in Preparation Example 7, its average pore size, macropore ratio, etc. are too small, and the swelling pore ratio is too high, which is manifested as Example 1 having significantly better final water immersion resistance and high-temperature water immersion resistance.

[0111] By comparing Example 1 with Comparative Example 1, it is shown that fillers without a regenerated cellulose layer on the surface cannot improve the water immersion resistance of tile adhesives; and by further comparing Comparative Example 2, it is not difficult to find that even if a regenerated cellulose layer is introduced on the surface of the filler, if the regenerated cellulose layer is relatively dense and does not have a pore structure, it is also difficult to obtain good anti-slip, bonding performance, and good water immersion resistance and high-temperature water immersion resistance. Further comparing Comparative Example 3, it is not difficult to find that if cellulose is added in a fiber state rather than in a special structure coated on the surface of the filler, it is also unable to solve the water immersion resistance problem of tile adhesives; further comparing Comparative Example 4 with Comparative Example 5, it can be found that whether only coarse fillers or only fine fillers are added, the anti-slip performance of tile adhesives and the water immersion resistance will decrease.

[0112] In summary, by adding a filler whose surface is coated with a regenerated cellulose layer, and the surface of the regenerated cellulose layer must have a porous structure, the tile adhesive can have good water resistance and even high temperature water resistance, and also has good initial bonding properties.

[0113] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A highly water-resistant, single-component, strong penetrating paste-like tile adhesive, characterized in that: According to parts by mass, it includes at least the following components: 100-200 parts of binder emulsion; 650-850 parts of inorganic filler; 50-150 parts of water; Thickener 3-15 parts; The inorganic filler comprises a coarse filler and a fine filler, wherein the coarse filler comprises coarse inorganic particles with a particle size of 250-800 μm and a coarse regenerated cellulose layer coated on the coarse inorganic particles, and the fine filler comprises fine inorganic particles with a particle size of 100-150 μm and a fine regenerated cellulose layer coated on the fine inorganic particles, and both the coarse regenerated cellulose layer and the fine regenerated cellulose layer are provided with moisture absorbing pores.

2. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 1, characterized in that: In the inorganic filler, the mass ratio of the inorganic particles to the regenerated cellulose layer is 10:2-3.

3. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 1, characterized in that: The average pore diameter of the moisture absorption pores is 50-200 nm, and the pore area of ​​the moisture absorption pores accounts for no less than 20%.

4. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 3, characterized in that: Among the moisture absorbing pores, those with a pore size greater than 150 nm are permeation pores, and those with a pore size not greater than 150 nm are swelling pores, and the number of the swelling pores accounts for a greater proportion than the number of the permeation pores.

5. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 4, characterized in that: The ratio of the swelling pores to the total number of the hygroscopic pores is 55-70%, and the ratio of the pores with a pore diameter greater than 300 nm to the total number of the hygroscopic pores is 1-5%.

6. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 1, characterized in that: According to the weight percentage, 1-5 parts of bactericide, 1-5 parts of dispersant and 0.5-2 parts of defoamer are also added to the tile adhesive.

7. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 1, characterized in that: The added mass ratio of the coarse filler to the fine filler is 1.5-3.5, the mass ratio of the inorganic filler to the effective mass of the binder emulsion is 8-13, and the effective mass of the binder emulsion is the product of the added mass of the binder emulsion and the solid content.

8. The process for preparing the highly water-resistant single-component strong penetrating paste-like tile adhesive according to any one of claims 1 to 7, characterized in that: The process steps include: S1, preparation of inorganic filler, preparing a modifying liquid and respectively blending the coarse inorganic particles and the fine inorganic particles with the modifying liquid to obtain a slurry, then placing the slurry in a solidifying liquid to solidify the modifying liquid by phase separation, and then placing it in a regeneration bath to form a coarse regenerated cellulose layer covering the coarse inorganic particles and a fine regenerated cellulose layer covering the fine inorganic particles, to obtain an inorganic filler covered with a regenerated cellulose layer; S2, mixing, according to the ratio, first preliminarily blend the binder emulsion and water to obtain a mixed emulsion, then heat the mixed emulsion to 50-70°C, then preliminarily blend the coarse filler and the fine filler into a mixed inorganic filler and add it to the heated mixed emulsion, the temperature of the inorganic filler is heated to 10-20°C higher than the temperature of the mixed emulsion, then add the remaining materials and stir evenly and cool to room temperature.

9. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 8, characterized in that: The step S1 specifically includes the following steps: S11, preparing a modifying liquid, wherein the modifying liquid comprises cellulose acetate, a porogen and a solvent, wherein the content of cellulose acetate in the modifying liquid is 10-15wt%, and the amount of the porogen added is 0.3-0.5 times the amount of the cellulose acetate added; S12, mixing, filling the packing bed with the coarse inorganic particles or the fine inorganic particles, and then filtering the modified liquid with the packing bed to make the modified liquid adhere to the inorganic particles to obtain a slurry, and the temperature of the mixing process is controlled at 10-20° C.; S13, solidification and phase separation, filtering the solidified liquid through a filler bed filled with slurry to promote phase separation and solidification of the modified liquid to obtain initial particles, wherein the solidified liquid is at least one of water, methanol and ethanol; S14, post-treatment, placing the initial particles in a regeneration bath to hydrolyze the cellulose acetate and regenerate it into regenerated cellulose, wherein the regeneration bath is an aqueous sodium hydroxide solution.

10. The highly water-resistant single-component strong penetrating paste-like tile adhesive according to claim 9, characterized in that: Before the step S13, the solvent vapor is filtered through a packed bed filled with slurry for 10-30 seconds. The solidifying liquid is a methanol aqueous solution, and the volume proportion of methanol is 20-30%.

Citation Information

Patent Citations

  • Tile adhesive based on ground granulated blast furnace SLAG (GGBFS)

    WO2024023063A1

  • Ceramic tile adhesive

    CN106145827A

  • Ceramic tile interface agent

    CN107601985A